After the nursery: Regional and broad‐scale movements of sharks tagged in the Caribbean. (10th August 2020) - Legare, Bryan; DeAngelis, Bryan; Skomal, Gregory
Abstract: Broad‐scale movements (10s–100s km) of highly migratory species, such as sharks, present unique management challenges as fish migrate across international boundaries, thereby exposing them to different levels of anthropogenic pressure. Lemon sharks and blacktip sharks are well‐studied throughout their range in the western North Atlantic, but broad‐scale movements in the Caribbean region are largely unknown. Utilizing 10 years (2004–2014) of acoustic and conventional tagging data, this study presents the post‐nursery movements of young of the year (YOY) and juvenile blacktip ( n = 198) and lemon ( n = 130) sharks tagged in the United States Virgin Islands (USVI). A total of five (2.5%) blacktip sharks were recaptured by recreational and commercial fishers in the greater Caribbean and as far north as the southeastern coast of the United States, moving between 2 and 2, 200 km and crossing a minimum of six international boundaries. Of the acoustically tagged blacktip ( n = 88) and lemon ( n = 45) sharks, 28 (32%) and 16 (24%), respectively, were detected outside the boundaries of the nursery area in which they were tagged, dispersing throughout the USVI territory; blacktip sharks were acoustically detected beyond territorial waters as far as Florida, United States (1, 881 km). Both species transited through local marine protected areas but did not establish residency resulting in little protection. This is the first study to examine connectivity between blacktip shark populations of the USVI and the east coast of the United States.